Read the students' notes (Journal of Parents and Teachers, 2026)
When lecturers wonder whether students are understanding what they hear—so that they can capture it in writing in their notes—the question inevitably arises as to whether they are explaining things properly. This is what has happened at some Japanese and American universities during summer courses for new students and also for those wishing to improve their learning in class. The lecturers decided to read the students’ notes and realised that some were ‘not listening’ properly, others were listening and understanding but ‘not retaining’ what they had heard, and others ultimately ‘could not reproduce’ clearly what the lecturer had said. The lecturers changed the way they explained things.
Keywords: listen; understand; remember; repeat; explain; take notes